ICG-001, an Inhibitor of the β-Catenin and cAMP Response Element-Binding Protein Dependent Gene Transcription, Decreases Proliferation but Enhances Migration of Osteosarcoma Cells - Geoffroy Danieau; Sarah Morice; Sarah Renault; Régis Brion; Kevin Biteau; Jérôme Amiaud; Marie Cadé; Dominique Heymann; Frédéric Lézot; Franck Verrecchia; Françoise Rédini; Bénédicte Brounais-Le Royer (MDPI AG, 2021)
High-grade osteosarcomas are the most frequent malignant bone tumors in the pediatric population, with 150 patients diagnosed every year in France. Osteosarcomas are associated with low survival rates for high risk patients (metastatic and relapsed diseases). Knowing that the canonical Wnt signaling pathway (Wnt/β-catenin) plays a complex but a key role in primary and metastatic development of osteosarcoma, the aim of this work was to analyze the effects of ICG-001, a CBP/β-catenin inhibitor blocking the β-catenin dependent gene transcription, in three human osteosarcoma cell lines (KHOS, MG63 and 143B). The cell proliferation and migration were first evaluated in vitro after ICG-001 treatment. Secondly, a mouse model of osteosarcoma was used to establish the in vivo biological effect of ICG-001 on osteosarcoma growth and metastatic dissemination. In vitro, ICG-001 treatment strongly inhibits osteosarcoma cell proliferation through a cell cycle blockade in the G0/G1 phase, but surprisingly, increases cell migration of the three cell lines. Moreover, ICG-001 does not modulate tumor growth in the osteosarcoma mouse model but, rather significantly increases the metastatic dissemination to lungs. Taken together, these results highlight, despite an anti-proliferative effect, a deleterious pro-migratory role of ICG-001 in osteosarcoma.